If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1 = 8x + 2 Reorder the terms: -1 + 7x = 8x + 2 Reorder the terms: -1 + 7x = 2 + 8x Solving -1 + 7x = 2 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -1 + 7x + -8x = 2 + 8x + -8x Combine like terms: 7x + -8x = -1x -1 + -1x = 2 + 8x + -8x Combine like terms: 8x + -8x = 0 -1 + -1x = 2 + 0 -1 + -1x = 2 Add '1' to each side of the equation. -1 + 1 + -1x = 2 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 2 + 1 -1x = 2 + 1 Combine like terms: 2 + 1 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3
| X-3-3x=3(1+x) | | y^4+12y^2+36=0 | | n/-15=5.3 | | 5(2x+6)=55 | | 1.6=4y+20.4 | | 2cos(x)-3x=0 | | 3x+4=9.5 | | n/14.3=-5 | | -0.166666666667= | | 0.5(y+8)=2(y-1) | | 7+8q=7q | | H=-16t^2+24t+40 | | -2x-1=2x+15 | | n/-12.168=-2 | | z+iz+1=0 | | 12(n+8)=132 | | 10(x+3)-9x-4=x-5+3 | | 4x-15=7x-60 | | (7x+15)=8x | | 2(x-4)=35 | | 3/r=12/17 | | y=(7+5k)x | | 4x^2+28x^3=0 | | 3k-5=7k+7 | | 2a+9=22249 | | 4x-31+2x=11 | | ln(3.2)=x | | 2(c+6)=c-13 | | 7y-8+6y+1= | | 13x+8-10x=65 | | x/-6=1-(-4) | | 4x+y+2xy+6y-2x= |